Strengthening the Legal Framework of Sharia Rural Bank (BPRS) to Support the MSME Resilience in Indonesia - Miftah Idris; Danang Wahyu Muhammad (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy; however, limited access to financing and regulatory constraints hinder their optimal development. The Sharia Rural Bank (BPRS) has significant potential to support MSME resilience, yet its effectiveness remains constrained by weaknesses in the legal system. This study aims to analyze and formulate strategies to strengthen the legal system of BPRSs to enhance MSME resilience in Indonesia.   Methods: This research employs a normative legal method and a qualitative approach, drawing on statutory and conceptual sources. Primary legal materials include laws and regulations governing Islamic banking, while secondary materials include academic literature and legal doctrines. Data were collected through library research and analyzed using Lawrence M. Friedman’s legal system theory, which encompasses legal structure, legal substance, and legal culture. Results: The findings indicate that the increasing trend of non-performing financing (NPF), institutional limitations, regulatory inconsistencies, and low levels of Islamic financial literacy weaken the effectiveness of BPRS in supporting MSMEs. It can be concluded that strengthening the legal structure, harmonizing legal substance, and improving legal culture are essential to optimize the role of BPRS in enhancing MSME resilience. Conclusion and suggestion: This study contributes by offering a holistic legal framework grounded in Friedman’s theory to support policy reform, institutional strengthening, and the development of Islamic financial literacy, thereby advancing MSME sustainability.